2019
DOI: 10.1016/j.celrep.2019.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Select Septate Junction Proteins Direct ROS-Mediated Paracrine Regulation of Drosophila Cardiac Function

Abstract: SUMMARY Septate junction (SJ) complex proteins act in unison to provide a paracellular barrier and maintain structural integrity. Here, we identify a non-barrier role of two individual SJ proteins, Coracle (Cora) and Kune-kune (Kune). Reactive oxygen species (ROS)-p38 MAPK signaling in non-myocytic pericardial cells (PCs) is important for maintaining normal cardiac physiology in Drosophila. However, the underlying mechanisms remain unknown. We find that in PCs, Cora and Kune are altered in abundance in respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Our study unravels the mechanistic basis of a metabolic role of the PCs, quite distinct from their normal nephrocytic function, in regulating cardiac activity in Drosophila . Studies in the recent past identified that elevated levels of pericardial ROS, in a p38-dependent manner, regulates the function of the neighboring cardiomyocytes involving two septate junction proteins, Cora and Kune ( 46 ). However, the underlying mechanism remains elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Our study unravels the mechanistic basis of a metabolic role of the PCs, quite distinct from their normal nephrocytic function, in regulating cardiac activity in Drosophila . Studies in the recent past identified that elevated levels of pericardial ROS, in a p38-dependent manner, regulates the function of the neighboring cardiomyocytes involving two septate junction proteins, Cora and Kune ( 46 ). However, the underlying mechanism remains elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Somewhat surprisingly, many SJ proteins are also required for the development of the dorsal vessel (heart), even though there is no SJ formed in this tissue [ 74 ]. The Drosophila embryonic heart is a linear organ composed of two rows of cardiomyocytes, the cells which contract to pump hemolymph through the organism, surrounded by two layers of pericardial cells, which have secretory, regulatory, and filtration roles [ 75 , 76 , 77 , 78 , 79 ]. Although SJs are not found in the dorsal vessel, two clear roles within the dorsal vessel have emerged for SJ proteins: in cell-cell adhesion and as effectors of reactive oxygen species-mediated paracrine regulation of cardiac function [ 77 , 80 ].…”
Section: Developmental Functions Of Sj Genesmentioning
confidence: 99%
“…In addition to the adhesive roles played by this wide set of SJ proteins, a critical role in regulating the structure and function of the dorsal vessel has been identified for a much smaller set of SJ proteins: Cora and the claudin Kune. These proteins were identified as sensitive to levels of reactive oxygen species (ROS) in pericardial cells, a characteristic not possessed by any of the other SJ proteins tested, nor by other members of the Protein 4.1 family [ 77 ]. The ROS signaling cascade acts through proteins such as the p38a MAP kinase in the pericardial cells to regulate critical processes in the neighboring cardiomyocytes [ 82 ].…”
Section: Developmental Functions Of Sj Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…New lines of evidence show that ROS signaling can be transferred in a diffusion-independent fashion from donor cells to nearby cells [135]. For instance, pericardial ROS were shown to directly modulate the expression of cell adhesion and cytoskeleton molecules that facilitate interaction between the pericardial cells and cardiac myocytes [136]. In addition, extracellular vesicles such as exosomes that derived from CMs in response to H 2 O 2 were shown to exacerbate apoptosis of transplanted stem cells [137].…”
Section: New Insights Of Ros In Intercellular Communicationsmentioning
confidence: 99%